Data Envelopment Analysis for Productivity on Small and Medium Enterprise: A Measurement. (October 2019) - Sari, Rahmi M.; Erwin; Syahputri, Khalida; Fattah, Ghassan M.
Abstract: Every operator wants SME that can be work optimally, Thus the SME's productivity projection to have increasement. As a case study, this research conduct in the SMEs that worked in general printing. This research also pursues to measure the productivity of operators. Based on the results of the initial research obtained by the station that most requires physical work is the pod station. The work system in pod station has not designed yet. Therefore, a work system will be designed for the station. First, the operator productivity measurements are carried out. The method used to measure operator productivity is Data Envelopment Analysis. The analysis started by making cycle times, work presentations, and the number of products produced as variables to obtain optimal functions. During the observations made at the SMEs, productive operators were obtained who managed 83.69% on the operator I and II carriers on 79.34%. From the calculation of the DEA, the second operator has the value equal to 1 so that it has passed the threshold of expected quality.